The Impact of the Managerial Communication on the Organizational Culture - BARBU, Cătălin Mihail; ŞOMĂCESCU, Sabina Mădălina (Journal of Advanced Research in Economics and International Business, 2014)
The organizational culture is an issue much debated in the literature. The study of the organizational culture should offer us an insight on what makes an organization to perform. The managerial communication is adapted to a certain culture and blends with that culture to help organizations reach its objectives. Our study found out that managerial communication should adapt to the organizational culture instead of trying to change it quickly. This is the case especially for managers recruited from outside of the organization. Managerial communication can potentate the culture and bring out the desired behaviors of the members of the organization. The interaction between managerial communication and organizational culture should create a synergy for the organization.